Analisa Pengaruh Religiusitas, Kebanggaan Nasional, Perilaku Politis, Keadilan Perpajakan, Kepercayaan pada Pemerintah Terhadap Tax Morale - Filianto Nugraha Sau; Raden Arja Sadjiarto (Tax & Accounting Review, 2014)
Tax is the largesst Indonesia’s sector of income that used for financing the state activities. Therefore, the question of taxpayer’s motivation to pay tax and comply the tax rules must be answered immediately. This study aimed to know the affect of religiousity, national pride, political attitude, fairness of taxation, trust in government on Tax morale. This study used multiple linier regression with quantitative data that obtained from questionnaires filled by individual taxpayers who were doing business in Rungkut, Surabaya. There were 74 questionnaires that could be processed. This research showed that religiousity, national pride, fairness of taxation, trust in government had positive and significant affects on tax morale. Meanwhile, political attitude had positive affect but not significant on tax morale.